'The invisible enemy': disability, loneliness and isolation. Issue 7 (9th August 2018) - Macdonald, Stephen J.; Deacon, Lesley; Nixon, Jackie; Akintola, Abisope; Gillingham, Anna; Kent, Jacqueline; Ellis, Gillian; Mathews, Debbie; Ismail, Abolaji; Sullivan, Sylvia; Dore, Samouka; Highmore, Liz
Abstract: The aim of this article is to quantitatively explore the relationship between disability, emotional loneliness and social isolation. The data analysis presents a number of statistically significant findings which illustrate that disabled people (N = 250) were at increased risk of experiencing emotional loneliness and social isolation compared with the nondisabled group (N = 355). This study identifies a number of disabling barriers which result in this overrepresentation of disabled people. The study aims to move away from a pathological explanation of linking loneliness and social isolation to disability, in order to explain this occurrence from a barrier-based approach.